2015
DOI: 10.1097/dss.0000000000000213
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perception on the Usage of Smartphones for Medical Photography and for Reference in Dermatology

Abstract: Patients appear to have clear preferences in the equipment used for medical photography and acceptable applications of smartphones, highlighting the importance of feedback in shaping patient-physician interactions. In light of patient opinions on camera preferences, it may be prudent to make a conscientious effort to refrain from using smartphones as a camera in the clinical setting until patient concerns regarding its use can be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
2
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 7 publications
3
60
2
8
Order By: Relevance
“…reviewed the literature regarding patient perceptions towards medical photography and found that ‘patients generally find it acceptable to capture non‐identifiable photographs, to have their physicians use the photographs and to use the images for academic scholarship’ but that ‘patients generally find it unacceptable to photograph their genitalia, to use a photograph where they are identifiable or to distribute an identifiable photograph via the Internet’. The debate regarding the use of smartphones vs. cameras continues – in a cross‐sectional survey of adult patients in urban academic and private practice dermatology clinics in Chicago, the majority preferred a hospital‐owned camera (97.7%) over the use of personal photographing equipment including a physician's digital camera (27.5%) or a physician's smartphone camera (27.2%) . The preference for the use of an institution‐owned camera to personal camera/personal camera‐phone for medical photography is consistent with that found in another survey of 338 patients attending oral and maxillofacial surgery and plastic surgery clinics in Nigeria , and in a survey of 400 patients from dermatology settings in New York City .…”
supporting
confidence: 62%
“…reviewed the literature regarding patient perceptions towards medical photography and found that ‘patients generally find it acceptable to capture non‐identifiable photographs, to have their physicians use the photographs and to use the images for academic scholarship’ but that ‘patients generally find it unacceptable to photograph their genitalia, to use a photograph where they are identifiable or to distribute an identifiable photograph via the Internet’. The debate regarding the use of smartphones vs. cameras continues – in a cross‐sectional survey of adult patients in urban academic and private practice dermatology clinics in Chicago, the majority preferred a hospital‐owned camera (97.7%) over the use of personal photographing equipment including a physician's digital camera (27.5%) or a physician's smartphone camera (27.2%) . The preference for the use of an institution‐owned camera to personal camera/personal camera‐phone for medical photography is consistent with that found in another survey of 338 patients attending oral and maxillofacial surgery and plastic surgery clinics in Nigeria , and in a survey of 400 patients from dermatology settings in New York City .…”
supporting
confidence: 62%
“…5 In addition to the ethical and legal implications of using smartphones for photography, patients prefer the use of hospital owned cameras over smartphones or physician owned personal cameras due to the concerns of privacy and patient confidentiality. 6 In one study, 60% of patients felt written informed consent was necessary over verbal consent. 7 Finally, the authors found a range of opinions among responders about what makes a photograph identifiable, and therefore, subject to legal protection.…”
Section: Discussionmentioning
confidence: 98%
“…A similar study in New York City reported 91% of patients being comfortable with photography using a clinic‐owned camera compared to 32% who were comfortable with photography using a mobile device . The main concerns reported by patients related to confidentiality . Interestingly, younger patients were less comfortable than older patients with the use of mobile devices for medical photography .…”
Section: Discussionmentioning
confidence: 95%
“…In the authors' personal experience, the ability to capture clinical photographs during the consultation was generally well‐received by patients; however, not all patients feel comfortable with this practice. A survey of dermatology patients in Chicago revealed that nearly all (98%) patients found the practice of medical photography using a hospital‐owned camera to be acceptable, in contrast to only 27% who found photography using the dermatologist's personal smartphone acceptable . A similar study in New York City reported 91% of patients being comfortable with photography using a clinic‐owned camera compared to 32% who were comfortable with photography using a mobile device .…”
Section: Discussionmentioning
confidence: 99%